The hazard zone of Mount Merapi and the community’s perception of (in)securities - Haryani Saptaningtyas (Sustinere: Journal of Environment and Sustainability, 2024)
Human beings identify security based on their life experiences and their ability to calculate risk, determining the degree to  which risk is acceptable or unacceptable. Living years in a risk-prone area bears the sensitivity that enables adaptation to temporary risks, such as volcanic eruptions. Mount Merapi, located on Java Island, is considered one of the most dangerous volcanoes in the world. In the prone area, the perception of risk has been invented by a legal body, such as the government and Non-Governmental Organizations (NGOs), through hazard mitigation strategies that dominate the discourse. At the same time, the voices of local people are less prominent. Local communities tend to perceive the dichotomy concept of hope and despair in a contextual manner, which influences their sens of uncertainty. The article explores how security and danger are contextualized under specific times and conditions. The empirical study aims to understand the varying perceptions by focusing on translating the term “human security” into the local language. The concept of human security, introduced as an international framework, was introduced using a top-down approach, adopted by the government, and applied at the local level. Thus, managing their own risk, will enhance local security and become active agents in defining risk and formulating their coping strategies.